Mitochondrial regulation in the tumor microenvironment: targeting mitochondria for immunotherapy - Ahn, Minseo; Ali, Akhtar; Seo, Jae Ho (Frontiers in Immunology, 2024)
Mitochondrial regulation plays a crucial role in cancer immunity in the tumor microenvironment (TME). Infiltrating immune cells, including T cells, natural killer (NK) cells, and macrophages, undergo mitochondrial metabolic reprogramming to survive the harsh conditions of the TME and enhance their antitumor activity. On the other hand, immunosuppressive cells like myeloid-derived suppressor cells (MDSCs), regulatory T cells (Tregs), mast cells, and tumor-associated macrophages (TAMs) rely on mitochondrial regulation to maintain their function as well. Additionally, mitochondrial regulation of cancer cells facilitates immune evasion and even hijacks mitochondria from immune cells to enhance their function. Recent studies suggest that targeting mitochondria can synergistically reduce cancer progression, especially when combined with traditional cancer therapies and immune checkpoint inhibitors. Many mitochondrial-targeting drugs are currently in clinical trials and have the potential to enhance the efficacy of immunotherapy. This mini review highlights the critical role of mitochondrial regulation in cancer immunity and provides lists of mitochondrial targeting drugs that have potential to enhance the efficacy of cancer immunotherapy.